2010
DOI: 10.1088/0957-4484/21/40/405504
|View full text |Cite
|
Sign up to set email alerts
|

On-chip SQUID measurements in the presence of high magnetic fields

Abstract: We report a low temperature measurement technique and the magnetization data of a quantum molecular spin, by implementing an on-chip SQUID technique. This technique enables SQUID magnetometry in high magnetic fields, up to 7 T. The main challenges and the calibration process are detailed. The measurement protocol is used to observe quantum tunneling jumps of the S = 10 molecular magnet, Mn(12)-tBuAc. The effect of a transverse field on the tunneling splitting for this molecular system is addressed as well.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 25 publications
2
40
0
Order By: Relevance
“…Such a hybrid implementation with phosphorus donor electron spins could be challenging due to the large magnetic fields that are required, which could drive the Josephson junctions of the superconducting qubit normal, although junctions have been shown to operate successfully in fields up to 7 T [44]. One alternative is to utilize a different donor, like bismuth, with a large enough zero-field splitting to enable low-field measurements [45].…”
mentioning
confidence: 99%
“…Such a hybrid implementation with phosphorus donor electron spins could be challenging due to the large magnetic fields that are required, which could drive the Josephson junctions of the superconducting qubit normal, although junctions have been shown to operate successfully in fields up to 7 T [44]. One alternative is to utilize a different donor, like bismuth, with a large enough zero-field splitting to enable low-field measurements [45].…”
mentioning
confidence: 99%
“…The SQUIDs share a common ground (sketched as a white rectangle). Each SQUID has one I − V line shown in green for clarity in their narrowest region.can work under in-plane magnetic fields in the range of ∼Tesla [28][29][30] .Using this setup, we successfully measured the resonance signal of Gd 3+ S = 7/2 ions diluted in a CaWO 4 single crystal with a concentration of 0.05%. Moreover, the resonance is between the first and third excited states at T = 0.5 K, demonstrating high sensitivity for applications in spin control in multi-level quantum system.…”
mentioning
confidence: 99%
“…The planar Nb nano-SQUID in Fig. 1(b) do have a large intrinsic flux noise because of its large inductance, but can be operated in a high parallel magnetic field12. However, the system noise of 28 μФ 0 /Hz 1/2 has been limited by the room-temperature amplifier and not reached its intrinsic noise level yet.…”
Section: Resultsmentioning
confidence: 99%
“…Because the nano-SQUID can be directly coupled to a small sample in the magnetic field12131415, it has made a great contribution to the field of nano-magnetism16171819. Recently, it was demonstrated that a nano-SQUID can be integrated on the tip of a scanning SQUID microscope to perform high-resolution imaging over a sample surface2021222324.…”
mentioning
confidence: 99%